The advantages of applying the business triangulation model between Spain, China and Latin America. A win-win relationship for all poles - Parra Pérez, Agueda (UNISCI Journal, 2016)
Spain can play an important role in the process of internationalization of Chinese enterprises in Europe and Latin America thanks to the historical experience of Spanish multinationals in these regions. Given the good tune existing in the diplomatic relations between Spain and China, if Spain takes advantage of its privileged position compared to other European economies, China might be interested in getting the support of Spain in Latin America, thereby facilitating the implementation of cooperation initiatives among the three poles. The key points to build a win-win partnership, based on a triangular scheme, is the importance of a local partner for the Chinese enterprises in their expansion in Latin America, in addition to the expertise and know-how needed in business processes, being the Spanish companies the best positioned in these areas.